Der Nachlass Paul de Lagarde Orientalistische Netzwerke und antisemitische Verflechtungen - Behlmer, Heike; Gertzen, Thomas L.; Witthuhn, Orell (Europäisch-jüdische Studien - Beiträge, 2020)
Based on the legacy and published works of the Göttingen orientalist Paul de Lagarde (1827-1891), the contributors to this volume undertake a historical inventory of his life and scientific work, including its political aspects, especially Lagarde's anti-Semitism. Besides describing the history of German Ancient Near Eastern Studies, the book also furnishes a broader context against the backdrop of then-prevalent "völkisch" ideology.